PENGARUH METODE PICTORIAL RIDDLE TERHADAP HASIL BELAJAR IPA SISWA KELAS VIII SMP TAMAN DEWASA IBU PAWIYATAN - Lintan Fara; Hidayati Hidayati; Astuti Wijayanti (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2015)
The objective for this research is to recognize the differences between learning using Pictorial Riddle method and speech method by evaluating the result study of 8th grade science class students at Taman Dewasa Ibu Pawiyatan Junior High School. The research is Quasi Experiment. Its design is using Matched Group Pretest Posttest Design. Based on statistical calculation, the average post-test results for control class and experiment class are 58,296 and 71,036. Through this calculation, we have tcount around 2,469 with p-value 0,16 in scale 5%. Since 0,016 is less then 0,05 (0,016 < 0,05) means there is a significant different study result for science’s (IPA’s) students. By using whole calculation, we have post-test average score for control class and experiment class in row 13,963 and 17,036 in which are in normal curve include in middle and high categories. It means learning using Pictorial Riddle method gives better influence towards study result improvement for 8th grade students in learning science (IPA).